Risk of venous thromboembolism in patients with non‐Hodgkin lymphoma surviving blood or marrow transplantation. Issue 24 (30th August 2019) - Gangaraju, Radhika; Chen, Yanjun; Hageman, Lindsey; Wu, Jessica; Francisco, Liton; Kung, Michelle; Ness, Emily; Parman, Mariel; Weisdorf, Daniel J.; Forman, Stephen J.; Arora, Mukta; Armenian, Saro H.; et al.
Abstract : Background: Patients with non‐Hodgkin lymphoma (NHL) have an increased risk of venous thromboembolism (VTE), particularly when they are receiving treatment. Blood or marrow transplantation (BMT) is recommended for relapsed/refractory NHL, and the risk of VTE after these patients undergo BMT is uncertain. Methods: Patients with NHL who survived 2 years or longer after BMT were surveyed for long‐term health outcomes, including VTE. The median follow‐up was 8.1 years (interquartile range, 5.6‐12.9 years). The risk of VTE in 734 patients with NHL versus 897 siblings without a history of cancer and the risk factors associated with VTE were analyzed. Results: BMT survivors of NHL were at increased risk for VTE in comparison with siblings (odds ratio for allogeneic BMT survivors, 4.61; P  < .0001; odds ratio for autologous BMT survivors, 1.75; P  = .035). The cumulative incidence of VTE was 6.3% ± 0.9% at 5 years after BMT and 8.1% ± 1.1% at 10 years after BMT. In allogeneic BMT recipients, an increased body mass index (BMI; hazard ratio [HR] for BMI of 25‐30 kg/m 2, 3.52; 95% confidence interval [CI], 1.43‐8.64; P  = .006; HR for BMI > 30 kg/m 2, 3.44; 95% CI, 1.15‐10.23; P  = .027) and a history of chronic graft‐versus‐host disease (HR, 3.33; 95% CI, 1.59‐6.97; P  = .001) were associated with an increased risk of VTE. Among autologous BMT recipients, a diagnosis of coronary artery disease (HR, 5.94; 95% CI, 1.7‐20.71; P  = .005) and prior treatment with carmustine (HR, 4.91; 95% CI, 1.66‐14.51; P  = .004) were associated with increased VTE risk. Conclusions: Patients with NHL who survive BMT are at risk for developing late occurring VTE, and ongoing vigilance for this complication is required. Future studies assessing the role of thromboprophylaxis in high‐risk patients with NHL are needed. Abstract : The risk of venous thromboembolism remains high several years after blood or marrow transplantation for patients with non‐Hodgkin lymphoma. An increased body mass index and a history of chronic graft‐versus‐host disease are associated with an increased risk of venous thromboembolism in allogeneic blood or marrow transplantation recipients, whereas in autologous blood or marrow transplantation recipients, a history of coronary artery disease and prior treatment with carmustine are associated with high risk.